Socio - Ethical Problems of Development National Idea - Alimbetova Gulparshin (Zien Journals, 2021)
This article discusses the national idea and the scientific, theoretical and practical significance of its development, the relevance today, the need to rely on the socio - ethical development of the national idea, as well as the principles of the development of the national idea aimed at forming a family on the basis of spiritual communication and aimed at educating young people in the spirit of national values.
Keywords: national idea; value; spirituality; national value